Mobilization and hematopoietic stem cell collection in poor mobilizing patients with lymphoma: final results of the German OPTIMOB study - Kriegsmann, Katharina; Bittrich, Max; Sauer, Sandra; Tietze-Stolley, Carola; Movassaghi, Kamran; Grube, Matthias; Vučinić, Vladan; Wehler, Daniela; Burchert, Andreas; Schmidt-Hieber, Martin; Rank, Andreas; Dürk, Heinz A.; et al. (Transfusion medicine and hemotherapy, 2023)
Introduction: Successful mobilization and collection of peripheral hematopoietic stem cells (HSCs) are necessary for lymphoma patients eligible for myeloablative chemotherapy with subsequent autologous stem cell transplantation (ASCT). Albeit G-CSF alone or combined with chemotherapy is well-established methods for HSC mobilization, up to 40% of the patients fail to mobilize (poor mobilizer, PM). Plerixafor (PLX) is commonly used in PM patients resulting in increased migration of HSCs into peripheral blood and thus improves the collection outcome. Methods: The prospective, multicenter, open-label, non-interventional OPTIMOB study assessed mobilization and collection parameter of patients with lymphoma or multiple myeloma to get deep insights in the treatment of those patients in clinical routine focusing on PM patients. PM was defined as follows: (1) no achievement of ≥20 CD34+ progenitor cells/µL before first apheresis, (2) PLX administration at any time point during the observational period, (3) reduction of the initially planned CD34+ progenitor cell yield as necessity due to failed mobilization or HSC collection, and (4) no performance of apheresis due to low CD34+ progenitor level. Primary objective of the study was to assess mobilization success by the proportion of PM patients achieving >2 × 106 CD34+ progenitor cells/kg body weight on the first day of apheresis. Here, the data of the lymphoma cohort are presented. Results: Out of 238 patients with lymphoma documented in the study, 32% were classified as PM. 87% of them received PLX. Demographic data revealed no obvious differences between PM and good mobilizing (GM) patients. All patients were treated highly individualized prior to mobilization. Majority of all PM patients were able to undergo apheresis (95%) and reached their individual requested CD34+ progenitor cell target (72%). 57% of the PM patients achieved >2.0 × 106 CD34+ progenitor cells/kg body weight on day 1 of apheresis and nearby 70% of them underwent ASCT. Median time to engraftment was similar in PM and GM patients of the lymphoma cohort. Conclusions: Majority of PM patients with lymphoma were successfully mobilized and underwent ASCT. Most of them received PLX during the study.
Gesehen am 08.07.2024